Organic synthesis engineering - Doraiswamy, L. K. (Topics in chemical engineering (Oxford University Press), 2001)
1. Introduction and structure of the book. Part I: Reactions and Reactors in Organic Synthesis: Basic Concepts. 2. Rates and equilibria in organic reactions: The thermodynamic and extrathermodynamic approaches. 3. Estimation of properties of organic compounds. 4. Reactions and reactors: Basic concepts. 5. Complex reactions. Part II: Catalysis in Organic Synthesis and Technology. 6. Catalysis by solids, 1: Organic intermediates and fine chemicals. 7. Catalysis by solids, 2: The catalyst and its microenvironment. 8. Homogeneous catalysis. 9. Asymmetric synthesis. Part III: Reactor Design for Hom.